Actualizing the tri-nga (ngerti, ngrasa, nglakoni) teachings in public accountants - Wardani, Dewi Kusuma; Hurek, Georgia Rostin Ellshadday (Proceeding International Conference on Accounting and Finance, 2024)
The research aims to determine the suitability of Ki Hadjar Dewantara’s teachings, namely tri-nga (ngerti, ngrasa, nglakoni) when actualized in public accountants. Study this is study descriptive qualitative with use technique primary data collection. Data collection begins with interviews semi-structured with two public accountants at their respective Public Accounting Firms and also a Tamansiswaan lecturer from the Bachelorwiyata Tamansiswa University who acts as a validator. Results study This show that there is conformity with the teachings of tri-nga (ngerti, ngrasa, nglakoni) when actualized in public accountants.